DYNAMICS SYSTEM ANALYSIS AND MODELING ON CRANE BRAND THREE DIMENSIONS (3D) WITH LOADING COSTS - Moh Khairudin (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2013)
This paper presents the development of a dynamic modelling of a three-dimensional (3D) crane with payload. A 3D crane with simultaneous travelling, traversing, and hoisting is considered. The dynamic equations of motion of the crane system are derived using the Lagrange’s method and represented in nonlinear differential equations. Simulation is performed using Matlab/Simulink to investigate the dynamic behaviour of the system both in time and frequency domains. System responses including positions of rail, trolley and payload, and payload sway angle are obtained and analyzed. The results show for sway angle, exhibits significant and persistent sway angle of ±0.09 rad. On the other hand, the sway angle, shows a significant initial sway angle of ±0.07 rad. Then the system coscillates with a persistent angle of ± 0.009 rad.